PHILOSOPHICAL FOUNDATIONS OF SAFETY IN CIVIL AVIATION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Ensuring flight safety in civil aviation is one of the priority tasks of modern society, aimed not only at achieving technical reliability, but also at strengthening passenger confidence in air transportation. The article examines the philosophical aspects of flight safety, considers its ethical, epistemological and ontological foundations. Particular emphasis is placed on the analysis of the influence of the human factor, technological innovations and regulatory mechanisms on ensuring safety. The author proposes an interdisciplinary approach combining philosophical and technical knowledge to develop a sustainable concept of safety in aviation.
Keywords: safety, civil aviation, epistemology, ontology, technological progress, human factor.